ANALYSIS OF CUSTOMER RETENTION STRATEGIES FOR SMALL AND MEDIUM-SIZED FRIED CHICKEN BUSINESSES IN JAKARTA: THE MEDIATING ROLE OF CUSTOMER SATISFACTION BASED ON PRODUCT QUALITY, SERVICE - Anindita Fadhillah (PT. Jurnal Center Indonesia Publisher, 2025)
The height competition in the sector business Micro, Small and Medium Enterprises (MSMEs) fried chicken in Jakarta demands perpetrator business for improve retention strategies customers, one of them through increased purchase interest repeat. Research This aim analyze influence quality products, service quality, and systems payment on purchase interest repeat, with satisfaction customer as intervening variables. Research quantitative this use Structural Equation Modeling (SEM) approach based on Partial Least Squares (PLS) with sample of 100-150 respondents MSMEs fried chicken customers in Jakarta. Test results hypothesis show that satisfaction customer own significant and positive influence​ on purchase interest repeat. Next, quality products and systems payment proven in a way direct influential positive and significant to satisfaction customers. Meanwhile that, variable quality products, service quality, and systems payment no show influence significant direct​ on purchase interest repeat. Findings this indicates that satisfaction customer play a role important as variables mediation. Strategy to increase purchase interest repeat must focused on efforts reach customer satisfaction. this is can achieved with maintain quality superior products (especially​ consistency of taste and texture), provides quality good service, as well as ensure system efficient and diverse payments. With​ thus, satisfaction customer is key main bridging​ influence quality products, service quality, and systems payment on purchase interest repeat to MSMEs fried chicken customers in Jakarta.